Cost-quality tradeoff in nurse staffing: an exploration of USA hospitals facing market competition. Issue 5 (23rd March 2022) - Peng, Xiaosong (David); Ye, Yuan; Fan, Raymond Lei; Ding, Xin (David); Chandrasekaran, Aravind
Abstract : Purpose: This research aims to explore the fine-grained relationships between nurse staffing and hospital operational performance with respect to care quality and operating costs. The authors also investigate the moderation effect of competition in local hospital markets on these relationships. Design/methodology/approach: A six-year panel data is assembled from five separate sources to obtain information of 2, 524 USA hospitals. Fixed-effect (FE) models are used to test the proposed hypotheses. Findings: First, nurse staffing is initially associated with improved care quality until nurse staffing reaches a turning point, beyond which nurse staffing is associated with worse care quality. Second, a similar pattern applies to the relationship between nurse staffing and operating costs, although the turning point is at a much lower nurse staffing level. Third, market competition moderates the relationship between nurse staffing and care quality so that the turning point of nurse staffing will be higher when the degree of competition is higher. This shift of turning point is also observed in the relationship between nurse staffing and operating costs. Practical implications: The study identifies three ranges of nurse staffing in which hospitals will likely experience simultaneous improvements, a tradeoff or simultaneous decline of care quality and operating costs when investing in more nursing capacity. Hospitals should adjust nurse staffing levels to the right directions to achieve better care or reduce operating costs. Originality/value: Nurses constitute the largest provider group in hospitals and profoundly impact care quality and operating costs among all health care professionals. Optimizing the level of nurse staffing, therefore, can significantly impact the care quality and operating costs of hospitals.